Platanthera jiuwanshanensis (Orchidaceae), a new species from Guangxi, China - Qin, Ying; Huang, Yu-Song; Meng, Tao; Liu, Yan (Phytotaxa, 2020)
Platanthera jiuwanshanensis, a new species of Orchidaceae from Guangxi, China is described and illustrated. The new species resembles P. fujianensis, P. guangdongensis, P. minor and P. zijinensis, but it can be clearly distinguished from P. fujianensis, P. guangdongensis by the distinct characters in lateral sepals, lip, spur and column, and from P. minor, P. zijinensis by the distinct characters in rootstock, lip and leafless plant. Detailed morphological descriptions, colour photographs, distribution and diagnostic comparisons etc. are provided here.